ESTUDO PRELIMINAR DA POTENCIALIDADE DO AQUÍFERO SERRARIA NA ÁREA SUL DO ESTADO DE ALAGOAS - CAVALCANTE, A.T.; BARROSO, C.M.R.; WANDERLEY, P.R.DE.M.; SANTOS, R.C. DE.A.L.; SANTOS, R.J.Q. (Águas Subterrâneas, 1994)
RESUMO NÃO DISPONÍVEL